2013
DOI: 10.1136/archdischild-2012-303062
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ventilation in children: longitudinal trends and outcomes

Abstract: The paediatric LTV population has expanded significantly over 15 years. Future planning of paediatric hospital and community services, as well as adult services, must take into account the needs of this growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
135
8
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(170 citation statements)
references
References 21 publications
13
135
8
3
Order By: Relevance
“…9 Several single-center studies conducted in Canada reported a rising prevalence of ventilator-assisted children. 10,11 Although a report from the Provincial Respiratory Outreach Program in British Columbia 12 indicated the prevalence to be 9.5/100,000 adults in a single province, no comprehensive national data describe prevalence of such individuals.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several single-center studies conducted in Canada reported a rising prevalence of ventilator-assisted children. 10,11 Although a report from the Provincial Respiratory Outreach Program in British Columbia 12 indicated the prevalence to be 9.5/100,000 adults in a single province, no comprehensive national data describe prevalence of such individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This has given rise to a new pediatric population represented by young patients on LTMV-H, be it invasive (IMV) or non-invasive (NIV), that has been growing more rapidly in the last few years, especially the latter subgroup [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries the last two decades have seen a gradual increase in the prevalence of pediatric patients on long-term mechanical ventilation at home (LTMV-H) [1][2][3][4][5][6][7][8][9][10][11][12] as a result of advances in medicine and technology affording these children a longer survival [1][2][3][4][7][8][9]11,12]. This has given rise to a new pediatric population represented by young patients on LTMV-H, be it invasive (IMV) or non-invasive (NIV), that has been growing more rapidly in the last few years, especially the latter subgroup [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…And this will become an ever increasing important medical care issue as advances in NIV technology and application have allowed more pediatric and adult patients with underlying nocturnal hypoventilation secondary to obesity or NMD the potential for long-term home NIV care outside of a hospital or skilled nursing facility. 4,5 …”
mentioning
confidence: 99%
“…We know that there is signifi cant morbidity and mortality in patients with underlying nocturnal hypoventilation secondary to obesity or NMD left untreated, 2 and there is longitudinal evidence showing improvement in quality of life and morbidity and mortality in youth when NIV initiation is successful. [3][4][5][6] However there are many barriers which must be overcome for successful initiation and use of NIV long-term home care. 7,8 It is important to pinpoint and overcome barriers to initiation of NIV in both youths and adults, as an early pattern of adherence to CPAP therapy is a signifi cant predictor of subsequent adherence.…”
mentioning
confidence: 99%